Te Rua - Barclay, Barry; O'shea, Rory; Attewell, Warrick; Wi Kuki Kaa; Meisner, Günter; Kaa, Peter
Some carvings of ancestors, taken from a Maori settlement in 1880, show up in a Berlin museum. Peter (Peter Kaa), a performing poet, wants to take the carvings back to his people. With the help of Rewi (Wi Kuki Kaa), an international lawyer, he is assisted in his fight. "Te Rua" is a passionate film about a quest for spiritual guardianship. The narrative is a bit overloaded with charactors and events, but not enough clear detail, so that the point of many scenes is muddled or lost, but it does contain emotional power. Filmed in Berlin, Wellington, Cape Palliser and the Wairarapa coast. [www.amazon.co.uk]